A 12‐week exercise programme has a positive effect on everyday executive function in young people with Down syndrome: a pilot non‐randomised controlled trial. Issue 12 (13th September 2022) - Shields, N.; Mizzi, N.; Buhlert‐Smith, K.; Strydom, A.; Prendergast, L.; Hocking, D. R.
Abstract: Background: Exercise has the potential to reduce cognitive decline in people with Down syndrome by maximising their cognitive function. The aim of the study was to determine the effect of regular exercise on cognitive functioning in young people with Down syndrome. Method: People with Down syndrome were eligible if aged between 13 and 35 years and enrolled to participate in an exercise programme (called FitSkills ). The intervention was a 12‐week community‐based exercise programme completed with a student mentor. Outcomes were assessed before (week 0) and immediately after (week 13) the intervention. Executive functioning (planning, response inhibition, attention shifting) was assessed using Tower of London, Sustained Attention to Response Task, CANTAB Intra‐extra Dimensional Set Shift Test, Cognitive Scale for Down Syndrome, and Behaviour Rating Inventory of Executive Function (BRIEF). Working memory was assessed using the CANTAB Paired Associates Learning task, and information processing speed was assessed using the Motor Screening Task. Outcomes were analysed using ANCOVA with the baseline measure as the covariate. Results: Twenty participants (9 women; mean age 23.6 ± 6.6 years) enrolled. Between‐group differences, in favour of the experimental group, were found for the global executive composite score of the BRIEF (mean difference −4.77 units, 95% CI −9.30 to −0.25). There were no between group differences for any other outcome measured. Conclusion: Participation in a 12‐week exercise programme was effective in improving everyday executive functions in young people with Down syndrome. These preliminary findings need to be confirmed in future randomised controlled trials of community‐based exercise with larger sample sizes.